2008
DOI: 10.1007/s11255-008-9419-7
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the clinical utility of transperineal urethrosphincteric block (TUSB) in outpatient rigid cystoscopy: a single-blind, randomized study

Abstract: This study demonstrates that TUSB is an effective and safe method in significantly relieving the pain associated with outpatient rigid cystoscopy. TUSB may offer urologists and anesthetists an alternative way to achieve pain control besides intraurethral lidocaine jelly during rigid cystoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although some studies in the literature preferred the way of measuring pain status at different stages of cystoscopy, this study decided to assess pain both during and 30 min after the procedure because it would be more practical and reliable 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies in the literature preferred the way of measuring pain status at different stages of cystoscopy, this study decided to assess pain both during and 30 min after the procedure because it would be more practical and reliable 10 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, no significant side-effects were reported. 10 However, in this study, infiltration from the perineum to the prostate apex requires experience and does not seem practical for the patient and the healthcare team. Thus, the practice of the current study is significantly more practical and easier to apply.…”
Section: Ta B L E 2 Patient Satisfaction Values Of Groupsmentioning
confidence: 95%
“…Although some studies in the literature preferred the way of measuring pain status at different stages of cystoscopy, this study decided to assess pain both during and 30 min after the procedure because it would be more practical and reliable. 10 Some studies suggest that the intraurethral administration of lidocaine is ineffective and that its administration does not provide sufficient absorption. 8,[11][12][13] Most of the specified studies were done with a flexible cystoscope, and it is observed that evaluations were made only 5 and 10 min after the procedure in rigid cystoscopy studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is believed that length of the stricture is not important and can be safely conducted under local urethral anesthesia(4,5), performing optical urethrotomy under general or regional anesthesia provides a great confidence to the urologists (5). Several authors have shown that OIU can be performed comfortably by various local anesthesia techniques including topical anesthesia, spongiosum block, transperineal and urethrosphincteric blocks with good analgesic effects (3,6,7). These techniques offer several advantages like the elimination of the anxiety and discomfort associated with general anesthetic induction and the avoidance of expected risks due to general or spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%